Digital workplace technology intensity: qualitative insights on employee wellbeing impacts of digital workplace job demands - Marsh, Elizabeth; Perez Vallejos, Elvira; Spence, Alexa (Frontiers in Organizational Psychology, 2024)
IntroductionDigital workplace technologies are powerful enablers in modern organizations but can also threaten employee wellbeing. Drawing on the Job Demands-Resources (JD-R) model, this study explores digital workplace job demands, including hyperconnectivity and overload, and their association with health impairment.MethodsUsing a qualitative approach, semi-structured interviews were conducted with 14 employees to capture their experiences of these phenomena. A Critical Realist Reflexive Thematic Analysis was employed to investigate tendencies among digital workers and to draw theoretical links that might reveal underlying mechanisms.ResultsFive overarching themes were identified: hyperconnectivity, techno-overwhelm, digital workplace hassles, Fear of Missing Out, and techno-strain. A connecting thread between these themes is the new concept we label Digital Workplace Technology Intensity, mirroring the dynamics of the existing construct of work intensity.DiscussionThe findings extend JD-R theory by highlighting the wellbeing challenges posed by digital workplace job demands. They emphasize the need for organizations to address the mental and physical health ramifications of the dark side of digital working.